Antifungal effect of nine selected medicinal plants against crop pathogenic fungi - Freddy Kuok San, Yeo; Siew Ting, Ling; S. Uvanappria, Sathasivam; Mohd Razip, Asaruddin; Hashimatul Fatma, Hashim; Lee San, Lai (Malaysian Society for Microbiology, 2022)
Aims: Plant diseases caused by pathogens are threatening crop yield. Agrochemicals are used extensively to curb pathogens. Efforts to reduce the usage of agrochemicals are needed for sustainable agriculture. This study was aimed to screen medicinal plants possessing antifungal properties against crop pathogenic fungi. Methodology and results: Sequential extraction using absolute n-hexane, ethyl acetate and methanol was performed on nine selected medicinal plants to obtain crude extract. An antifungal assay using these crude extracts was performed on Fusarium solani, Collectotrichum musae and two isolates of Pyricularia oryzae. The assay showed that medicinal plant species with all three types of crude extract inhibited the growth of all three pathogenic fungal species tested. The inhibitory effects of crude extracts were not only fungal species dependent but also isolate dependent. Conclusion, significance and impact of study: Antifungal effect of nine selected medicinal plant species was observed against the three tested fungal pathogens. These research findings suggest that the selected medicinal plant species may serve as a potential source for the development of new biofungicide products